2005
DOI: 10.21273/jashs.130.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Endodormancy Break in Almond Flower Buds by a Correlation Model Using the Average Temperature of Different Day Intervals and its Application to the Estimation of Chill and Heat Requirements and Blooming Date

Abstract: Almond (Prunus amygdalus Batsch.) blooming date is determined by the temperatures during the dormancy period, from the onset of endodormancy to just before blooming. In this work we have developed a model, based on several years data, to estimate the mean transition date from endodormancy to ecodormancy in 44 almond cultivars covering the whole range of almond bloom, through the significance of correlation coefficients between the temperatures occurring during dormancy and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 14 publications
4
56
1
3
Order By: Relevance
“…Estimations under laboratory conditions have been deemed to be of low practical significance with regard to fruit trees under orchard conditions because the environmental variables are unnaturally constant, rather than fluctuating (Dennis, 2003;Luedeling et al, 2009a). So we chose the use of the statistical method of Alonso et al (2005) to estimate the mean date from endo-to ecodormancy shift. This method is based on the different influence of warm and cold temperatures on flowering date depending on their impact on dormancy phases: heat accumulation during the forcing phase would advance flowering; hence, a negative correlation would be expected between temperature in this phase and flowering date.…”
Section: Estimating Endo-to Ecodormancy Shift Datementioning
confidence: 99%
See 2 more Smart Citations
“…Estimations under laboratory conditions have been deemed to be of low practical significance with regard to fruit trees under orchard conditions because the environmental variables are unnaturally constant, rather than fluctuating (Dennis, 2003;Luedeling et al, 2009a). So we chose the use of the statistical method of Alonso et al (2005) to estimate the mean date from endo-to ecodormancy shift. This method is based on the different influence of warm and cold temperatures on flowering date depending on their impact on dormancy phases: heat accumulation during the forcing phase would advance flowering; hence, a negative correlation would be expected between temperature in this phase and flowering date.…”
Section: Estimating Endo-to Ecodormancy Shift Datementioning
confidence: 99%
“…Thus, following Alonso et al (2005), daily maximum, minimum, and mean temperatures were averaged day by day over different time periods (running means for the subsequent 5,10,15,20, 25 and 30 days intervals) and correlated with flowering dates expressed as day-of-year number for each apple cultivar in every phenological year from 1st October until 28th February. After Alonso et al (2005) the endo-to ecodormancy shift (endodormancy breaking date), was considered to be the day when the first statistically significant correlation occurs in a continued presence of negative correlations coefficients (Fig.…”
Section: Estimating Endo-to Ecodormancy Shift Datementioning
confidence: 99%
See 1 more Smart Citation
“…Predictions of bloom date in fruit and nut production have been hampered by the inability to model the heat requirement for bud development following the satisfaction of the chilling requirement. Much effort has been devoted to attempting to quantify and mechanistically describe the heat requirement for forcing of buds, however, the heat requirement of particular genotypes appears to be heavily dependent on the prevailing environmental conditions (Alonso et al 2005;Andres and Duran 1999;Gibson and Reighard 2002;Pawasut et al 2004). In particular, the ability of chilling temperatures to substitute for the heat requirement of buds has been observed in species as diverse as grape and Douglas fir (Harrington et al 2009;Mathiason et al 2009).…”
Section: Dam Genes Are Up-regulated By Short Photoperiodsmentioning
confidence: 99%
“…However, there are opposing findings and opinions in the literature about the importance of chilling temperatures for early spring phenology in temperate trees. In almonds, according to Alonso et al (2005), heat requirements were found to be more important for regulation of blooming time than chilling requirements in the cold climatic conditions of Zaragoza (north-east Spain). However, in south-east Spain, the almond flowering time was influenced more by chilling than by heat requirements (Egea et al 2003).…”
Section: Pheno-climatic Correlationsmentioning
confidence: 99%